PENDIDIDIKAN EMANSIPATORIS DAN MASYARAKAT MADANI - Rukiyati, Rukiyati; L. Andriyani, L. Andriyani (Jurnal Cakrawala Pendidikan, 2016)
The civil society is basically a society which is dialogueoriented and emancipato ya s well as independent in natuse. It is an arena where various social movements express themselves in groups to proceed with their interests. ’Fo come to such a society there needs to be a social transformation which involves, among others, education. All this time the educational realities in Indonesia have not heen adequate fol the formation of the cibil society. 1 herefore, there needs to be a refosniation of the educational pal adigm so that education which is emancipato ? iu nature is achieved. Habermas’ theory of co ununicationc an be one alternative means in the course of reforming the educational paradigm in Indonesia. The imple nentationo ft laber nas’t heory of communication in education can be made in the teaching-learning process. This process demands the fulfillment of the claims of communication concerning tr 1t1-r1i.g htness. sincerity, and comprehensibility. In the teaching-learning process which fdfils the claims of comnlunication will appear the dimensions of interest, discourse. consensus, and emancipation which bring the teacher and students together to a self- I eflection.